A Review on nanolubricant for refrigeration systems: Stability, thermophysical properties, and performance characteristics - Prayogo, Galang Sandy; Mamat, Rizalman; Ghazali, Mohd. Fairusham; Nugroho, Agus; Kozin, Muhammad; Muriban, Jackly (Universitas Muhammadiyah Magelang, 2024)
Many researchers have introduced nanolubricants in the field of refrigeration systems to improve performance. Nevertheless, academic literature lacks comprehensive explanations of the impact of nanoparticles on the physical phenomena that influence the refrigeration system. Several factors such as stability, agglomeration, and distribution can significantly affect the sustainability of performance. Hence, this work provides an analysis of the methods using nanolubricants to improve the performance of refrigeration systems. This study provides a comprehensive analysis of the performance parameters of the refrigeration system, including compressor work and coefficient of performance (COP), when utilizing nanolubricants. The study findings suggest that including nanolubricants in the refrigeration system can enhance the heat transfer coefficient. Hence, nanolubricants are identified as the most promising contenders for enhancing the efficiency of the refrigeration system.